A high precision phase extraction method in heterodyne interferometer based on FPGA. Issue 1 (1st November 2022) - Deng, Wen; Peng, Xifeng
Abstract: The high-precision phase extraction method directly determines the final measurement performance of the heterodyne laser interferometer. This paper proposes a digital quadrature phase-locked (DQPL) method with sub-nanometer precision based on FPGA hardware and compiled on the LABVIEW FPGA platform. DQPL method can accurately extract the phase difference of the two optical signals in the heterodyne laser interferometer. The validity and stability of the method have been verified by simulations and experiments. The experimentally obtained measurement resolution is 0.074 nm, and the measurement standard deviation obtained by the Monte Carlo method is 0.22 nm.